Extended Results on Minimum Pendant Dominating Distance Graph Energy - Nataraj K; Puttaswamy; Purushothama S (Utilitas Mathematica, 2025)
Recently, we introduced the concept of minimum pendant dominating energy [19]. Building on that work, we now propose the concept of minimum pendant dominating distance energy, denoted by EPDd (G) for a graph G. We compute the minimum pendant dominating distance energies for several standard graphs, including the complete bipartite graph, star graph, bi-star graph, barbell graph, and cocktail party graph. Additionally, we establish both upper and lower bounds for EPDd (G).